A Real-time Search Structure and Classification Algorithm of Microblog Based on Partial Indexing - Jingbo Yuan; Bairong Wang; Shunli Ding (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
With the popularity and the rapid development of social networks, microblog has also obtained great attention and gotten wide application. Microblog may produce a large amount of information per second. The real-time search is a critical technology to timely get the latest high-quality information from microblog. A new real-time search framework based on meta-search engine and a query classification algorithm of microblog was put forward. The classification and indexing process is based on the partial indexing mechanism to improve retrieval efficiency. The classification algorithm divides queries into the candidate queries and the popular queries, and takes separate storage strategy. Test results show that the classification algorithm can reduce real-time search time and improve the efficiency of retrieval. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4497